2017
DOI: 10.3390/s17122751
|View full text |Cite
|
Sign up to set email alerts
|

Knee Impedance Modulation to Control an Active Orthosis Using Insole Sensors

Abstract: Robotic devices for rehabilitation and gait assistance have greatly advanced with the objective of improving both the mobility and quality of life of people with motion impairments. To encourage active participation of the user, the use of admittance control strategy is one of the most appropriate approaches, which requires methods for online adjustment of impedance components. Such approach is cited by the literature as a challenge to guaranteeing a suitable dynamic performance. This work proposes a method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…The gait phases considered are as follows: initial contact (heel contact); mid-stance (flat foot contact); terminal stance (heel off); and swing (foot-off). More details about this control system can be found in our previous work [36], where also are shown validation results with volunteers. The results showed that this control system is able to execute movements according to the volunteers' movement intention, providing suitable reference patterns for gait as well as proper torques for the motion classes considered here.…”
Section: Admittance Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The gait phases considered are as follows: initial contact (heel contact); mid-stance (flat foot contact); terminal stance (heel off); and swing (foot-off). More details about this control system can be found in our previous work [36], where also are shown validation results with volunteers. The results showed that this control system is able to execute movements according to the volunteers' movement intention, providing suitable reference patterns for gait as well as proper torques for the motion classes considered here.…”
Section: Admittance Controllermentioning
confidence: 99%
“…Safety and usability evaluation with healthy subjects and post-stroke patients are also addressed [21,27,[37][38][39]. On the other hand, studies conducted about muscles and inertial patterns during walking with these devices have focused on the evaluation of lower-limb muscle activity [36,37], with few studies evaluating other muscles related to maintenance of dynamic postural equilibrium during gait, such as trunk muscles [40]. It is worth commenting that the muscular activity gives a representation of which action users of these devices are attempting to execute.…”
Section: Admittance Controllermentioning
confidence: 99%
“…Controlling the motion enables the actuators to be controlled; thus, the tracking of the position [30] or velocity [21] can be done. However, it would be better if the output reference is an adaptive one, especially in the stance phase [93]. Because there is only one reference, it is assumed that the position of the ankle joint is the same the entire time.…”
Section: Output Reference: Fixed Versus Adaptivementioning
confidence: 99%
“…Although terminal stance phase was not detected in all trials, this is also reported in other studies, due the gait dynamic (Wentink et al, 2013;Agostini et al, 2014), the admittance modulation was able to generate a G pattern to obtain a SC performance as shown in Figure 5. It allows adapting different impedances at the knee joint during the phases stance and swing (Villa-Parra et al, 2017). For gait phase recognition in pathological cases, such as stroke survivors that present different footswitch patterns (Agostini et al, 2014), an alternative for gait phase detection is using data fusion considering the knee angle, initial movement from inertial sensors or sEMG signals to detect the gait phases (Lee et al, 2015).…”
Section: Motion Classmentioning
confidence: 99%